Akupresur Sebagai Alternatif Mengurangi Nyeri Haid (Disminorea) pada Remaja Putri - Heni Hirawati Pranoto; Avisha Ladyana Fitri; Dewi Setyani; Amanda Putri (Universitas Ngudi Waluyo, 2022)
Dysmenorrhea is menstruation accompanied by pain and is often complained of by 40-80% of young women. Dysmenorrhea can be treated by giving pharmacological therapy with non-steroidal anti-inflammatory drugs and non-pharmacological therapy with acupressure techniques. Acupressure is done by massaging techniques on certain body meridians to stimulate the natural ability to heal oneself by restoring the balance of positive energy in the body. Based on the data obtained after conducting the pretest using a questionnaire, it was found that 90% of the adolescents who attended the counseling in Banyubiru did not know about dysmenorrhea and acupressure which are techniques in complementary therapy to overcome dysmenorrhea. Therefor the purpose of this complementary service activity for adolescents is to provide counseling as a basis for knowledge about the importance of complementary care to reduce menstrual pain in adolescents, namely acupressure. The method in this community service is to use 4 stages, namely determining respondents, filling out the pretest, implementation and evaluation. What is delivered is by providing materials using leaflet media and demonstrations using porbandus tools. Respondents taken were young women, amounting to 6 people. The result of the community service that has been carried out is an increase in the knowledge of young women about acupressure massage from before and after the counseling is given. AbstrakDismenore adalah menstruasi yang disertai nyeri dan sering dikeluhkan oleh 40-80% remaja putri. Dismenore dapat diatasi dengan pemberian terapi farmakologi dengan obat anti inflamasi non steroid dan terapi non farmakologi dengan teknik akupresur. Akupresur dilakukan dengan teknik pemijatan pada meridian tubuh tertentu untuk merangsang kemampuan alami menyembuhkan diri sendiri dengan mengembalikan keseimbangan energi positif dalam tubuh. Berdasarkan data yang diperoleh setelah dilakukan pretest dengan menggunakan kuesioner, diketahui bahwa 90% remaja yang mengikuti penyuluhan di Banyubiru tidak mengetahui tentang dismenore dan akupresur yang merupakan teknik terapi komplementer untuk mengatasi dismenore. Untuk itu tujuan dari kegiatan layanan komplementer bagi remaja ini adalah untuk memberikan penyuluhan sebagai dasar pengetahuan tentang pentingnya perawatan komplementer untuk mengurangi nyeri haid pada remaja yaitu akupresur. Metode dalam pengabdian masyarakat ini menggunakan 4 tahapan yaitu penentuan responden, pengisian pretest, pelaksanaan dan evaluasi. Yang disampaikan adalah dengan memberikan materi menggunakan media leaflet dan demonstrasi menggunakan alat porbandus. Responden yang diambil adalah remaja putri yang berjumlah 6 orang. Hasil dari pengabdian masyarakat yang telah dilakukan adalah peningkatan pengetahuan remaja putri tentang pijat akupresur dari sebelum dan sesudah diberikan penyuluhan.